HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU MERAWAT BAYI DENGAN STATUS KESEHATAN BAYI POST PERAWATAN NICU DI RSUD W. Z. JOHANNES KUPANG - Florentianus Tat (CHMK NURSING SCIENTIFIC JOURNAL, 2018)
Abstrak This study entitled the relationship between mother's knowledge level and mother's behavior in caring for infant health status of post-nursing baby NICU in Prof. Dr. W. Z. Johannes Hospital in Kupang-NTT, Indonesia, which is motivated by the still high morbidity and mortality of infants and children. Infant mortality can occur at home or in health facilities. Families especially mothers have an important role to prevent infant mortality and death including after treatment at NICU. The objectives of the study looked at the relationship between mother's knowledge level and mother's behavior in caring for infants on post-nurse health status of NICU "in RSUD Prof. Dr. W. Z. Johannes Kupang. Methods of quantitative research with cross-sectional approach, on 39 respondents of mothers who have children treated in NICU, data collection using questionnaires, analysis of dektriptif and simple linear regression. The majority of researches were age <20 and> 35 years (54%), elementary school education (46%). work of housewife (69%), baby is male (77%), infant weight enough category 2000 - 2500 gram (54%), length of day care category enough 3-6 days (54%), mother's knowledge in care of infants sufficient category (53%), mother's behavior in caring for good category baby (87%). The conclusions of maternal knowledge in treating infants after NICU care were categorized as good (53). Maternal behavior in caring for infants after NICU care is included in either category (87%). Infant health status in terms of infant weight after NICU treatment included in the category is quite good (2000 - 2500 grams). There is a significant relationship between knowledge and behavior of maternal care with infant health status in terms of infant weight (p = 0.000). *) Keywords: Knowledge, Behavior, infant health status. DAFTAR PUSTAKA Depkes RI. 2009. Profil Kesehatan Indonesia tahun 2008. Pusat Data Kesehatan: Jakarta. Dinas Kesehatan Kota Kupang. 2010. Profil Kesehatan Kota Kupang Tahun 2013. Tersedia di web dinkes.kotakupang.web.id. diakses pada tanggal 23 Oktober 2015. Ekayanti Hafidah Ahmad,dkk. 2012. Faktor determinan status kesehatan bayi neonatal di Rskdia siti fatimah makassar. Jurnal KesMas UAD. Vol. 6, No. 3, September 2012 : 144-211. Diakses tanggal 23 Oktober 2015. Kuswanti, Ina. 2014. Pengaruh Pendidikan Kesehatan Terhadap Keterampilan Menyusui Pada Ibu Post Partum Ditinjau Dari Paritas. Jurnal Kesehatan “Samodra Ilmu” Vol. 05 No. 02 Juli 2014. Diakses tanggal 23 Oktober 2015. Asrining S., dkk, 2003, Perawatan Bayi Risiko Tinggi, Penerbit Buku Kedokteran EGC, Jakarta. Arikunto, S. 2006. Prosedur Pnelitian: suatu Pendekatan Praktek. Edisi. Revisi VI. Rineka Cipta: Jakarta Bherman, Richard E, dkk. 1999. Ilmu Kesehatan Anak Nelson. Vol.1. EGC: Jakarta Meadow, Roy & Simon Newell. 2005. Lecture Notes Pediatrika: Edisi Ketujuh. Erlangga: Jakarta Suriadi & Rita Yuliani. 2010. Buku Pegangan Pediatric Klinik: Asuhan Keperawatan Pada Anak. Sagung seto: Jakarta Wong, Dona L. 2008. Pedoman Klinis Keperawatan Pediatric. EGC: Jakarta